2017
DOI: 10.1186/s13014-017-0899-4
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy (SBRT) for definitive treatment and as a bridge to liver transplantation in early stage inoperable Hepatocellular carcinoma

Abstract: Background and PurposeStereotactic body radiotherapy (SBRT) is an emerging modality for definitive treatment of Hepatocellular carcinoma (HCC).Materials and MethodsThis retrospective study included all early stage HCC patients who were not candidates for primary resection and/or local therapy, treated with SBRT between 11/2011 and 1/2016.ResultsTwenty-three patients were included. The median age was 62 years; 70% males; 30% females; 70% viral hepatitis carriers; 100% cirrhotic; 13 Child Pugh [CP]-A and 10 [CP]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 25 publications
(37 reference statements)
2
53
0
Order By: Relevance
“…In our own experience with SBRT for HCC, we reported favorable outcomes using SBRT as de nitive treatment or as a bridge to liver transplantation in pts with early stage inoperable HCC [9]. Median prescribed dose to the tumor was 54 Gy (range, 30-54Gy) with median overall-survival for the transplanted patients not reached and 23 months for the patients who were not transplanted.…”
Section: Discussionmentioning
confidence: 96%
“…In our own experience with SBRT for HCC, we reported favorable outcomes using SBRT as de nitive treatment or as a bridge to liver transplantation in pts with early stage inoperable HCC [9]. Median prescribed dose to the tumor was 54 Gy (range, 30-54Gy) with median overall-survival for the transplanted patients not reached and 23 months for the patients who were not transplanted.…”
Section: Discussionmentioning
confidence: 96%
“…Reports, which focus on the post-SBRT pathology are limited. SBRT as a bridging treatment prior to liver transplantation showed a complete pathological response rate of 27-63% [26][27][28][29] . The complete pathological response rate in our study was comparable to that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic local control rates exceed 85% (►Table 1). [84][85][86][87][88][89] In studies assessing for radiographic response only a few months after SBRT, response rates may be lower 90 but are likely underestimations as SBRT response can take up to 6 months or longer. 91 Pathologic response rates were variable, ranging from 37 to 70%.…”
Section: Bridge Therapy and Downstagingmentioning
confidence: 99%
“…Compared with other liver-directed therapies, SBRT was associated with lower toxicity and decreased hospitalization days 96 but tended to cause more liver function impairment. 93 Surgical complication rates were not increased in patients receiving SBRT as bridge therapy, 85,86,88,93 although one study identified a single patient for whom a modification of surgical approach was needed. 84 Few reports are dedicated to describing the efficacy of SBRT in downstaging patients to become eligible for transplant.…”
Section: Bridge Therapy and Downstagingmentioning
confidence: 99%